Epoxy/Glass Fiber Nanostructured p- and n-Type Thermoelectric Enabled Model Composite Interphases - George Karalis; Kyriaki Tsirka; Lazaros Tzounis; Christos Mytafides; Lampros Koutsotolis; Alkiviadis S. Paipetis (Applied Sciences, 2020)
This experimental study is associated with the modification of glass fibers with efficient, organic, functional, thermoelectrically enabled coatings. The thermoelectric (TE) behavior of the coated glass fiber tows with either inherent p semiconductor type single wall carbon nanotubes (SWCNTs) or the n-type molecular doped SWCNTs were examined within epoxy resin matrix in detail. The corresponding morphological, thermogravimetric, spectroscopic, and thermoelectric measurements were assessed in order to characterize the produced functional interphases. For the p-type model composites, the Seebeck coefficient was +16.2 μV/K which corresponds to a power factor of 0.02 μW/m∙K2 and for the n-type −28.4 μV/K which corresponds to power factor of 0.12 μW/m∙K2. The p–n junction between the model composites allowed for the fabrication of a single pair thermoelectric element generator (TEG) demonstrator. Furthermore, the stress transfer at the interphase of the coated glass fibers was studied by tow pull-out tests. The reference glass fiber tows presented the highest interfacial shear stress (IFSS) of 42.8 MPa in comparison to the p- and n-type SWCNT coated GF model composites that exhibited reduced IFSS values by 10.1% and 28.1%, respectively.